Fates of potassium during co-pyrolysis of corn stalk and plastic film components - Chao Fan; Jing Liu; Junxia Wang; Jian Li; Zixi Han; Xiaoqiang Cui; Zhanjun Cheng; Beibei Yan; Guanyi Chen; Jingang Yao (Biomass and Bioenergy, 2027)

A machine learning-based dual system coupling model of catalytic-gasification: a calcium-based case study with mechanistic interpretability - Yadong Ge; HongRu Li; Zaixin Li; Zhi Wang; Xiaoqiang Cui; Beibei Yan; Junyu Tao; Zhanjun Cheng; Ningbo Gao (Bioresource Technology, 2027)

Machine learning-assisted quorum sensing molecules regulate growth progression and bioactivity of an oxygenic photobiofilm for non-aeration greywater purification - Beibei Wu; Libo Xia; Qian Li; Xiaocai Cui; Ting Ran; Yangrui Huang; Yun Zhou (Bioresource Technology, 2026)

Techno-economic and environmental assessment of biomass-to-gasoline production via dual fluidized bed gasification coupled with a syngas-to-gasoline process - Hongyu Cui; Yuwen Shao; Guanyi Chen; Beibei Yan; Zhanjun Cheng; Weiming Yi; Baofeng Zhao; Lingyu Tai; Sunu Herwi Pranolo; Obie Farobie; Paolo De Filippis; Benedetta De Caprariis; et al. (Chemical Engineering Journal, 2026)

New insights into the temporal speciation of phosphorus during anaerobic digestion of wetland biomass wastes - Fan Yu; Junxia Wang; Zhi Wang; Lan Mu; Xutong Wang; Qianqian Guo; Xiaoqiang Cui; Yanjun Hu; Beibei Yan; Guanyi Chen (Bioresource Technology, 2026)

CXCL12/CXCR4 signaling governs ischemic neurovascular pathophysiology and repair: a multidimensional contextual analysis - Shahram Eisa-Beygi; Hao Wu; Kui Cui; Kulandaisamy Arulsamy; Bo Zhu; Beibei Wang; Bandana Singh; Krishan Gupta; Jianing Gao; Scott Wong; Joyce Bischoff; Hanqiang Deng; et al. (Angiogenesis, 2026)

Corrigendum to “Port pollution prediction and management via multi-view intelligent computing: A case study of Tianjin Port”[regional studies in marine science 95(2026)104805] - Tong Xue; Yong Li; Qiang Mei; Yundi Bai; Yang Yang; Lei Cui; Peng Wang; Beibei Zhang; Shaohua Wang (Regional Studies in Marine Science, 2026)

Metabolic complementarity in LAB-yeast co-fermentation associates with enhanced ester aroma in cream cheese - Beibei Duan; Yueyue Zhou; Siyu Wang; Ling Yan; Yujie Lin; linze Li; Bin Xue; Rui Huang; Yipan Zhang; Yue Cui; Nan Wu; Xiangting Kong; et al. (Food Research International, 2026)

Corrigendum to “Catechol-induced assembly to enhance the performance of antimicrobial peptide fully” [Chem. Eng. J. Volume 524 (2025) 169195] - Xiao Wang; Yuanyuan He; Beibei Cui; Yuan Feng; Jingjing Lin; Xirui Long; Yanchao Wang; Zhen Li; Feng Luo; Jiehua Li; Hong Tan (Chemical Engineering Journal, 2026)

A mini review on micro/nanobubble-mediated interfacial enrichment and adsorption-coupled pollutant removal: Core mechanisms, application scenarios, and feasibility - Xianglin Chang; Fuxing Yan; Aofan Wang; Shouqiang Wan; Xiaoqiang Cui; Beibei Yan; Guanyi Chen; Ning Li (Chemical Engineering Journal, 2026)

Ankyrin-repeat transmembrane protein WAI-1 confers multiple disease resistance in wheat by activating autoimmunity - Qiuhong Wu; Wenling Li; Yongxing Chen; Huaizhi Zhang; Delin Li; Zhan Li; Fei Xiong; Guanghao Guo; Lei Dong; Xuejia Cui; Jingzhong Xie; Ping Lu; et al. (Science China Life Sciences, 2026)

Targeting the TOPK-STAT3 pathway in keratinocytes and mast cells mediates the therapeutic attenuation of Atopic dermatitis - Xiaohan Du; Xianshuai Shi; Qian He; Zheng Yuan; Longzhen Cui; Beibei Tang; Shuang Zhao; Yafang Li; Lei Ma; Mee-Hyun Lee; Olesya S. Malyarenko; Juanjuan Xiao; et al. (Inflammation Research, 2026)

Study on the mechanism of fat coal compatibility driven by structure transformation - Xuhui Chen; Ruyuan Duan; Ruifang Hou; Xin Jin; Bo Wu; Yanfeng Shen; Beibei Cui; Liping Chang; Chunhao Liang; Xinjie Han; Meijun Wang (Fuel, 2026)

Correction to: Phyllosphere-specific fungal phylotypes enhance drought resistance to maintain functional stability in Populus euphratica - Beibei Chen; Juntuan Zhai; Jiajia Sun; Yifei Cui; Waqar Ali; Zhichao Xia (Plant and Soil, 2026)

Phyllosphere-specific fungal phylotypes enhance drought resistance to maintain functional stability in Populus euphratica - Beibei Chen; Juntuan Zhai; Jiajia Sun; Yifei Cui; Waqar Ali; Zhichao Xia (Plant and Soil, 2026)

Diversity loss of soil microbiome stimulates soil carbon emissions - Haibo Pan; Yingyi Fu; Hairong Tu; Yongxing Cui; Beibei Chen; Jiejun Qi; Ziheng Peng; Shi Chen; Chunling Liang; Jiai Liu; Xiaomeng Li; Min Gao; et al. (Soil Biology and Biochemistry, 2026)

Port pollution prediction and management via multi-view intelligent computing: A case study of Tianjin Port - Tong Xue; Yong Li; Qiang Mei; Yundi Bai; Yang Yang; Lei Cui; Peng Wang; Beibei Zhang; Shaohua Wang (Regional Studies in Marine Science, 2026)

Spatial planning based on the modeling the food-energy-water‑carbon nexus: A case study of the Yangtze River basin - Beibei Guo; Xian Zou; Yingxue Cui; Suchen Ying; Yinkang Zhou (Agricultural Systems, 2026)

Silencing of the Superaquaporin LvAQP11 Disrupts Salinity Tolerance, Molting Cycle, and Myofibril Organization in Litopenaeus vannamei - Zhongkai Wang; Guanghao Song; Shikui Zhang; Long Zhang; Beibei Wang; Kunpeng Zhao; Yanting Cui; Fei Liu; Renjie Wang; Yuquan Li (Fishes, 2025)
The Pacific white shrimp (Litopenaeus vannamei), a euryhaline crustacean of significant economic importance, is widely cultivated for its adaptability to diverse salinity levels. Aquaporins (AQPs) are membrane channel proteins that mediate the transport of water and small solutes across biological membranes. Among them, aquaporin 11 (AQP11) is classified as a superaquaporin, and its physiological roles remain unclear. In this study, RNA interference (RNAi) was employed to silence AQP11 expression in L. vannamei, followed by RNA-seq analysis to investigate transcriptomic responses. Differentially expressed genes (DEGs) were identified by comparing dsAQP11 and control groups. The LvAQP11 knockdown significantly increased mortality to 76.7% under acute high-salinity stress (50‰) but not under low-salinity conditions (10‰). Transcriptomic analysis revealed that LvAQP11 deficiency disrupted amino acid metabolism pathways and triggered endoplasmic reticulum stress, as evidenced by the upregulation of proteasome subunits and unfolded protein response genes. Furthermore, silencing LvAQP11 delayed molting progression in the premolt stages, accompanied by the significant upregulation of molt-inhibiting hormone (LvMIH1/5) and downregulation of retinoic acid X receptor (LvRXR). The long-term silencing of LvAQP11 did not affect the weight gain rate (WGR) or the specific growth rate (SGR) but induced muscle fiber disorganization and significantly increased muscle water content. RNA sequencing identified enriched carbohydrate and chitin metabolism pathways, indicating disrupted cytoskeletal dynamics and extracellular matrix integrity. Through this study, we elucidate the crucial roles of LvAQP11 in osmoregulation, molting, and muscle integrity in L. vannamei, providing novel insights into the multifunctional nature of superaquaporins beyond water transport.

Flavoromics analysis of effects of fresh mandarin fish storage methods on Chouguiyu (Chinese fermented mandarin fish) flavor and microbial correlations - Beibei Zhou; Minglin Wu; Yangyang Jiang; Yongxu Sun; Kai Cui; Jianfeng Lu (Food Research International, 2025)

Insight into the transformation of phosphorus in soil affected by microplastics: A review - Xuchen Zhang; Shicheng Dong; Junxia Wang; Kiran Yasmin Khan; Zhanjun Cheng; Xiaoqiang Cui; Jipeng Luo; Beibei Yan; Guanyi Chen (Environmental Research, 2025)

Catechol-induced assembly to enhance the performance of antimicrobial peptide fully - Xiao Wang; Yuanyuan He; Beibei Cui; Yuan Feng; Jingjing Lin; Xirui Long; Yanchao Wang; Zhen Li; Feng Luo; Jiehua Li; Hong Tan (Chemical Engineering Journal, 2025)

Evolution of phosphorus during co-pyrolysis of wheat straw and mulch film components - Chao Fan; Junxia Wang; Yuxin Yang; Jian Li; Xiaoqiang Cui; Zhanjun Cheng; Beibei Yan; Guanyi Chen; Jingang Yao (Chemical Engineering Journal, 2025)

Insight into transformation of phosphorus species in biomass gasification at different stages - Xuemei Fu; Beibei Yan; Jian Li; Yanshan Wang; Xiaoqiang Cui; Guanyi Chen; Wenzhu Wu; Li’an Hou (Bioresource Technology, 2025)

Reclamation of available phosphorus and separation of heavy metals from sewage sludge via FeCl3-assisted electrokinetic treatment and pyrolysis - Xutong Wang; Huwei Li; Junxia Wang; Wolfram Buss; Anna Bogush; Ondřej Mašek; Youjun Zhang; Fan Yu; Beibei Yan; Zhanjun Cheng; Xiaoqiang Cui; Guanyi Chen; et al. (Journal of Environmental Management, 2025)

A review on the production of nutrient-enriched biochar: Insights from the evolution of nitrogen, phosphorus, and potassium - Xiaoqiang Cui; Xufeng Li; Junxia Wang; Xutong Wang; Fan Yu; Gaixiu Yang; Shiwei Xu; Zhanjun Cheng; Qianying Yang; Beibei Yan; Guanyi Chen (Critical Reviews in Environmental Science and Technology, 2025)

Boosted chlorate hydrogenation reduction via continuous atomic hydrogen - Yilin Lu; Xiangdong Zhu; Aodi Li; Cheng Cheng; Beibei Xiao; Peixin Cui; Yujun Wang; Dongmei Zhou (Journal of Hazardous Materials, 2025)

Integrated learning framework for enhanced specific surface area, pore size, and pore volume prediction of biochar - Chao Chen; Yongjie Hu; Yadong Ge; Junyu Tao; Beibei Yan; Zhanjun Cheng; Xuebin Lv; Xiaoqiang Cui; Guanyi Chen (Bioresource Technology, 2025)

Machine learning-based prediction of non-aeration linear alkylbenzene sulfonate mineralization in an oxygenic microalgal-bacteria biofilm - Libo Xia; Beibei Wu; Xiaocai Cui; Ting Ran; Qian Li; Yun Zhou (Bioresource Technology, 2025)

Differences in bacterial community structure and volatile flavor substance of industrial-scale tiger skin chicken feet stored at air packaging and vacuum packaging - Xingguang Chen; Beibei Chu; Wei Cui; Guo Jie; Yinghui Zhang; Hui Zhou; Baocai Xu; Qianhui Gu (Food Research International, 2025)

Visual large language model for wheat disease diagnosis in the wild - Kunpeng Zhang; Li Ma; Beibei Cui; Xin Li; Boqiang Zhang; Na Xie (Computers and Electronics in Agriculture, 2024)

Ground-based mobile imaging for detecting salt stress of cotton seedlings in the field - Jiayi Li; Peiqi Ren; Yanpeng Bi; Atoba Tolulope Opeyemi; Jie Cui; Yang Gao; Dapeng Ye; BeiBei Zhou; Haiyong Weng (Computers and Electronics in Agriculture, 2024)

Efficient reclamation of phosphorus from wetland biomass waste via liquid-recirculated hydrothermal carbonization and precipitation - Junxia Wang; Yuting Wang; Fan Yu; Jiangtao Wang; Xutong Wang; Jipeng Luo; Chao He; Xiaoqiang Cui; Beibei Yan; Guanyi Chen (Water Research, 2024)

Evaluating the spatiotemporal land ecological changes in the Yangtze-to-Huaihe Water Diversion Project area - Beibei Guo; Wei Li; Xuemin Kong; Tingting Cheng; Tingting Sun; Yingxue Cui (Environmental Science and Pollution Research, 2024)

Synergy of CoN3 and CuN3O2 sites in single atom-decorated biochar for peroxymonosulfate activation: Accelerating the production of SO4•− and •OH - Chuanbin Wang; Jingnan Tian; Yangli Cui; Ning Li; Xiaoqiang Cui; Beibei Yan; Guanyi Chen (Chemical Engineering Journal, 2024)

Microalgal extracellular polymeric substances (EPS) and their roles in cultivation, biomass harvesting, and bioproducts extraction - Yun Zhou; Xiaocai Cui; Beibei Wu; Ziqi Wang; Ying Liu; Tian Ren; Siqing Xia; Bruce E. Rittmann (Bioresource Technology, 2024)

Calcitriol attenuates lipopolysaccharide-induced neuroinflammation and depressive-like behaviors by suppressing the P2X7R/NLRP3/caspase-1 pathway - Changshui Wang; Changmeng Cui; Xin Xie; Beibei Chen; Lei Feng; Pei Jiang (Psychopharmacology, 2024)

Differentiation and quantification of extracellular polymeric substances from microalgae and bacteria in the mixed culture - Tian Ren; Yun Zhou; Xiaocai Cui; Beibei Wu; Bruce E. Rittmann (Water Research, 2024)

Heating rate effects on the coking properties evolution for varying rank coals: Insights into volatiles reaction and mass transfer - Beibei Cui; Meijun Wang; Zhihong Li; Xin Jin; Yanfeng Shen; Ting Li; Lunjing Yan; Liping Chang (Fuel, 2024)

Experimental investigation on the effect of vent film material and thickness and hydrogen fraction on explosion-venting features of H2/CO/Air mixtures within a horizontal duct - Beibei Qi; Haitao Li; Minggao Yu; Chengcai Wei; Jingyu Cui; Fuer Zhai (Process Safety and Environmental Protection, 2024)

In-situ study of the heating rate effects on covalent bonds conversion and pore/carbon microcrystal evolutions of coal molecule during coking - Beibei Cui; Meijun Wang; Mo Zheng; Zhihong Li; Xin Jin; Yanfeng Shen; Liping Chang (Fuel, 2024)

A comprehensive investigation on the structural transformation and dissolution loss reaction of coke during gasification in CO2 atmosphere - Beibei Cui; Meijun Wang; Zhihong Li; Xin Jin; Yanfeng Shen; Liping Chang (Fuel, 2024)

Pyrolysis of exhausted biochar sorbent: Fates of cadmium and generation of products - Xiaoqiang Cui; Yuxin Yang; Jiangtao Wang; Zhanjun Cheng; Xutong Wang; Kiran Yasmin Khan; Shiwei Xu; Beibei Yan; Guanyi Chen (Science of The Total Environment, 2024)

Assembly mechanisms and driving factors of aerobic denitrifying bacteria community with different seasons and rarity in the sediments of Baiyangdian Lake - Zhaoying Chen; Tinana Zhang; Ziwei Zhang; Lin Yue; Jiansheng Cui; Jiafeng Zhang; Shilei Zhou; Beibei Chai (Journal of Soils and Sediments, 2024)

Diverse ALS mutations and cross-and multiple-resistance to ALS and EPSPS inhibitors in flucarbazone‑sodium-resistant Bromus japonicus populations from Hebei province, China - Xian Xu; Bochui Zhao; Binghua Li; Beibei Shen; Zhizun Qi; Jianping Wang; Haiyan Cui; Silong Chen; Guiqi Wang; Xiaomin Liu (Pesticide Biochemistry and Physiology, 2024)

Coupling electrokinetic technique with hydrothermal carbonization for phosphorus-enriched hydrochar production and heavy metal separation from sewage sludge - Xutong Wang; Ondřej Mašek; Huwei Li; Fan Yu; Christian Wurzer; Junxia Wang; Beibei Yan; Xiaoqiang Cui; Guanyi Chen; Li'an Hou (Chemical Engineering Journal, 2024)

Trp-574-Leu mutation and metabolic resistance by cytochrome P450 gene conferred high resistance to ALS-inhibiting herbicides in Descurainia sophia - Xian Xu; Bochui Zhao; Binghua Li; Beibei Shen; Zhizun Qi; Jianping Wang; Haiyan Cui; Silong Chen; Guiqi Wang; Xiaomin Liu (Pesticide Biochemistry and Physiology, 2024)

A preliminary study on the quality evaluation of coking coal from its structure thermal transformation: Applications of fluidity and swelling indices - Beibei Cui; Bo Wu; Meijun Wang; Xin Jin; Yanfeng Shen; Liping Chang (Fuel, 2024)

Poly-adenine-mediated tetrahedral DNA nanostructure with multiple target-recognition sites for ultrasensitive and rapid electrochemical detection of Aflatoxin B1 - Kaixuan Wang; Nuanfei Zhu; Yumo Li; Hu Zhang; Beibei Wu; Jian Cui; Jun Tang; Zhugen Yang; Fang Zhu; Zhen Zhang (Analytica Chimica Acta, 2023)

Assessment of urban blue-green space cooling effect linking maximum and accumulative perspectives in the Yangtze River Delta, China - Yingxue Cui; Beibei Guo; Wei Li; Xuemin Kong (Environmental Science and Pollution Research, 2023)

Biofilm bioactivity affects nitrogen metabolism in a push-flow microalgae-bacteria biofilm reactor during aeration-free greywater treatment - Beibei Wu; Ting Ran; Sibei Liu; Qian Li; Xiaocai Cui; Yun Zhou (Water Research, 2023)

Enhanced mechanism of copper doping in magnetic biochar for peroxymonosulfate activation and sulfamethoxazole degradation - Chuanbin Wang; Haoxi Dai; Lan Liang; Ning Li; Xiaoqiang Cui; Beibei Yan; Guanyi Chen (Journal of Hazardous Materials, 2023)

In-situ elemental quantitative imaging in plant leaves by LA-ICP-MS with matrix-matching external calibration - Zewei Cui; Man He; Beibei Chen; Bin Hu (Analytica Chimica Acta, 2023)

Microbial niches and dynamics of antibiotic resistance genes in a bio-enhanced granular-activated carbon biofilm treating greywater - Ting Wei; Ziqi Wang; Ying Yang; Wanchen Xiang; Ying Liu; Beibei Wu; Xiaocai Cui; Bing Guo; Yun Zhou (Chemosphere, 2023)

Correction: Characteristics of land-subsidence evolution and soil deformation before and after the Water Diversion Project in Beijing, China - Kunchao Lei; Fengshan Ma; Beibei Chen; Yong Luo; Wenjun Cui; Yi Zhou; Fang Tian; Te Sha (Hydrogeology Journal, 2023)

Production of potassium-enriched biochar from Canna indica: Transformation and release of potassium - Guanyi Chen; Yuting Wang; Jiangtao Wang; Junxia Wang; Fan Yu; Qingxu Ma; Zhanjun Cheng; Beibei Yan; Yuchao Song; Xiaoqiang Cui (Waste Management, 2023)

Evaluating the threshold limit value of acceptable exposure concentration for exposure to bioaerosols in a wastewater treatment plant: Reverse-quantitative microbial risk assessment and sensitivity analysis - Beibei Cui; Dongzi An; Haojun Li; Xi Luo; Hao Zhu; Ming Li; Xiaojun Ai; Jiaxin Ma; Wajid Ali; Cheng Yan (Journal of Hazardous Materials, 2023)

Identification and functional characterization of caspases in turbot (Scophthalmus maximus) in response to bacterial infection - Tong Cui; Peng Liu; Xuan Chen; Zhe Liu; Beibei Wang; Chengbin Gao; Zhongyi Wang; Chao Li; Ning Yang (Fish & Shellfish Immunology, 2023)

Distribution and dynamics of antibiotic resistance genes in a three-dimensional multifunctional biofilm during greywater treatment - Ying Liu; Beibei Wu; Xiaocai Cui; Qingqing Ren; Tian Ren; Yun Zhou (Environmental Pollution, 2023)

Spatial and temporal dynamic response of abundant and rare aerobic denitrifying bacteria to dissolved organic matter in natural water: A case study of Lake Baiyangdian, China - Tianna Zhang; Zhaoying Chen; Ziwei Zhang; Shilei Zhou; Jiajing Meng; Zhe Chen; Jiafeng Zhang; Jiansheng Cui; Beibei Chai (Environmental Research, 2023)

Application of MXene-based materials in Fenton-like systems for organic wastewater treatment: A review - Chuanbin Wang; Jingya Ye; Lan Liang; Xiaoqiang Cui; Lingchao Kong; Ning Li; Zhanjun Cheng; Wenchao Peng; Beibei Yan; Guanyi Chen (Science of The Total Environment, 2023)

Genome-wide identification and functional characterization of inhibitor of nuclear factor-κB (IκB) kinase (IKK) in turbot (Scophthalmus maximus) - Zhe Liu; Peng Liu; Tong Cui; Xuan Chen; Beibei Wang; Chengbin Gao; Zhongyi Wang; Chao Li; Ning Yang (Fish & Shellfish Immunology, 2023)

Comprehensive understanding of guest compound intercalated layered double hydroxides: Design and applications in removal of potentially toxic elements - Shihao Cui; Yutao Peng; Xiao Yang; Xing Gao; Chung-Yu Guan; Beibei Fan; Xue Zhou; Qing Chen (Critical Reviews in Environmental Science and Technology, 2023)

pH-dependent microbial niches succession and antibiotic resistance genes distribution in an oxygen-based membrane biofilm reactor treating greywater - Beibei Wu; Qingqing Ren; Libo Xia; Ying Liu; Xiaocai Cui; Anqi Dai; Ting Wei; Yun Zhou (Environmental Research, 2023)

Effects of South-to-North Water Diversion Project on groundwater and land subsidence in Beijing, China - Kunchao Lei; Fengshan Ma; Beibei Chen; Yong Luo; Wenjun Cui; Long Zhao; Xinhui Wang; Aihua Sun (Bulletin of Engineering Geology and the Environment, 2023)

What are the disease burden and its sensitivity analysis of workers exposing to Staphylococcus aureus bioaerosol during warm and cold periods in a wastewater treatment plant? - Jiaxin Ma; Dongzi An; Beibei Cui; Manli Liu; Hao Zhu; Ming Li; Xiaojun Ai; Wajid Ali; Cheng Yan (Environmental Science and Pollution Research, 2022)

Water Boundary Detection for SAR Images Using Region-Based Active Contours with Salient Edge Energy - Baojun Guo; Jinlong Cui; Beibei Gao (Journal of the Indian Society of Remote Sensing, 2022)

Characteristics of land-subsidence evolution and soil deformation before and after the Water Diversion Project in Beijing, China - Kunchao Lei; Fengshan Ma; Beibei Chen; Yong Luo; Wenjun Cui; Yi Zhou; Fang Tian; Te Sha (Hydrogeology Journal, 2022)

Effects of phosphorus-containing material application on soil cadmium bioavailability: a meta-analysis - Yi Tan; Xue Zhou; Yutao Peng; Zijing Zheng; Xing Gao; Yan Ma; Shuo Chen; Shihao Cui; Beibei Fan; Qing Chen (Environmental Science and Pollution Research, 2022)

Mapping the research of energy subsidies: a bibliometric analysis - Zhen Wang; Yanwen Wang; Sha Peng; Beibei Niu; Can Cui; Junyi Wu (Environmental Science and Pollution Research, 2019)

Optimum design of level monitoring points for land subsidence - Yong Luo; Beibei Chen; Kunchao Lei; Ruilin Hu; Chao Ye; Wenjun Cui (Bulletin of Engineering Geology and the Environment, 2019)

Late Quaternary glaciations in the Cogarbu valley, Bhutanese Himalaya - Xu Peng; Yixin Chen; Gengnian Liu; Beibei Liu; Yingkui Li; Qing Liu; Yesong Han; Weilin Yang; Zhijiu Cui (Journal of Quaternary Science, 2019)
This study investigates the late Quaternary glacial history of the Cogarbu valley on the northern slopes of the Bhutanese Himalaya using 10 Be surface exposure dating. Five major glacial events were constrained based on 28 10 Be exposure ages. The equilibrium line altitude (ELA) of the oldest and most extensive glacial event (M5–M9) is ∼489 m lower than the present, followed by four other events (M4, M3, M2 and M1) with ELA depressions of ∼452, ∼200, ∼76 and ∼42 m, respectively. The exposure ages of the oldest glacial event (M5–M9) are ∼23.4–19.1 ka, corresponding to the global Last Glacial Maximum (gLGM). The second (M4, ∼15.8 ka) and the third oldest events (M3, ∼11.5 ka) coincide with the Heinrich‐1 and Younger Dryas event, respectively. The fourth oldest glacial event (∼1.2–0.82 ka) occurred during the Late Holocene. The latest glacial event (∼0.77–0.53 ka) represents the Little Ice Age glacial advances. These glacial events are broadly synchronous with those from other regions across the monsoon‐influenced Himalaya. All these events occurred during the cold periods, despite relatively dry conditions. It appears that temperature is the major factor driving glacial fluctuations since the gLGM in the Bhutanese Himalaya.

Total arsenic concentrations in Chinese children’s urine by different geographic locations, ages, and genders - Xuan Zhang; Beibei Wang; Xiaoyong Cui; Chunye Lin; Xitao Liu; Jin Ma (Environmental Geochemistry and Health, 2018)

Contact Angle Measurements: an Alternative Approach Towards Understanding the Mechanism of Increased Drug Dissolution from Ethylcellulose Tablets Containing Surfactant and Exploring the Relationship Between Their Contact Angles and Dissolution Behaviors - Tiaotiao Liu; Jingqiang Hao; Baixue Yang; Beibei Hu; Zhixiang Cui; Sanming Li (AAPS PharmSciTech, 2018)

Positive Selection of the Bat Interferon Alpha Gene Family - Guimei He; Beibei He; Paul A. Racey; Jie Cui (Biochemical Genetics, 2010)